2020
DOI: 10.1186/s12890-019-1035-z
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of circ-ABCB10 promotes sensitivity of lung cancer cells to cisplatin via miR-556-3p/AK4 axis

Abstract: Background Due to the acquired drug resistance, the potency of cisplatin-based chemotherapy is limited in lung cancer, which is a big obstacle in clinical treatment of lung cancer. Abundant evidence has revealed that circular RNAs (circRNAs) exerted facilitating or suppressive function on the tumorigenesis of multiple cancers. The oncogenic role of circ-ABCB10 in breast cancer and clear cell renal cell carcinoma has been validated in recent researches. However, the regulatory mechanism of circ-ABCB10 and its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…CircRNAs were abnormally expressed in different cancers (9,11). In lung cancer, studies found that the expressions of hsa_circ_0072083, CircZNF124, and CircABCB10 are up-regulated (12,14,15) but that of hsa_circ_11780, CircPTK2, and hsa_circ_0078767 are down-regulated (13,17,18). This study discovered the up-regulation of CircCHST15 in lung cancer tissues and cells, which was similar to the findings of Liu et al (16).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…CircRNAs were abnormally expressed in different cancers (9,11). In lung cancer, studies found that the expressions of hsa_circ_0072083, CircZNF124, and CircABCB10 are up-regulated (12,14,15) but that of hsa_circ_11780, CircPTK2, and hsa_circ_0078767 are down-regulated (13,17,18). This study discovered the up-regulation of CircCHST15 in lung cancer tissues and cells, which was similar to the findings of Liu et al (16).…”
Section: Discussionsupporting
confidence: 85%
“…In recent decades, evidence has increasingly proven that circRNAs play crucial parts in cancer development, including lung cancer (9)(10)(11). For example, CircZNF124 can promote the progression of nonsmall cell lung cancer cells by targeting mIR-337-3p (12); hsa_circ_0011780 inhibits the proliferation and metastasis of lung cancer (13); down-regulated CircABCB10 enhances the sensitivity of lung cancer cells to cisplatin (14); hsa_circ_0072083 could promote the effect of cisplatin on suppressing the growth of lung cancer (15). Furthermore, a recent study discovered that CircCHST15 (hsa_circ_0109320) is differentially expressed in gefitinib-treated lung cancer and might be a biomarker for the treatment of lung cancer in the future (16).…”
Section: Introductionmentioning
confidence: 99%
“…circ-ABCB10 (with 17 cricRNAD IDs, generated from ATP binding cassette subfamily B member 10) is a circRNA highly expressed in many cancers, including esophageal squamous cell carcinoma (ESCC), 43 oral squamous cell carcinoma, 44 lung cancer, 45 , 46 thyroid cancer, 47 BC, 48 and gliomas. 49 It acts as an oncogene by promoting cell proliferation, migration, and invasion while inhibiting cell apoptosis.…”
Section: Autophagy-related Circrna In Cancermentioning
confidence: 99%
“… 49 It acts as an oncogene by promoting cell proliferation, migration, and invasion while inhibiting cell apoptosis. 43 , 44 , 45 , 46 , 47 , 48 , 49 circ-ABCB10 also plays an important role in the development of tumor drug resistance. 45 , 50 The knockdown of circ-ABCB10 could restore the sensitivity of DDP-resistant lung cancer cells and increase DDP-induced apoptosis by the miR-556-3p/AK4 axis.…”
Section: Autophagy-related Circrna In Cancermentioning
confidence: 99%
See 1 more Smart Citation